PENERAPAN GANTI KERUGIAN TERHADAP TERDAKWA YANG DIPUTUS BEBAS BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA DI PENGADILAN NEGERI PEKANBARU - Flora Veronika; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The compensation is the right of suspects, accused and convicted as an embodiment of human rights, the dignity and the dignity of one of them is accused acquitted. Pekanbaru District Court there are many defendants were acquitted however, there was never any claim for damages. The purpose of this research are: first, to know the settings in the application for damages against the defendant were acquitted by the Code of Criminal Procedure, second, to determine the obstacles encountered in the implementation of compensation against the defendants acquitted by the Book of the Law Criminal Procedure in Pekanbaru District Court, Third, to know the efforts made to provide legal protection for a defendant in the application for damages against the defendant were acquitted by the Code of Criminal Procedure in Pekanbaru District Court.From the research there are three main issues that can be inferred. first, the setting of the application for damages against the defendants acquitted been regulated in Article 95 of the Criminal Procedure Code, the Indonesian Government Regulation Number 27 of 1983 on the Implementation of the Code of Criminal Procedure and the Decree of the Minister of Finance of the Republic of Indonesia Number: 983 / KMK.01 / 1983 December 31, 1983 on Procedures for the Payment of Compensation. Secondly, the obstacle in the application of damages against defendants acquitted by the Code of Criminal Procedure in the District Court Pekanbaru such rules can no longer be maintained, a complicated process, the amount of compensation is too little, the accused felt free after free, compensation is not included in the judgment. Third, efforts are being made to provide protection against the defendants in the application for damages against the defendant were acquitted by the Code of Criminal Procedure in the District Court of Pekanbaru, it can be done effort, such as revising legislation, make its own rules more binding, socialize regulation to the public, include the right to damages in the verdict, revising the compensation body, held monitoring to observe the performance of the police and the prosecutor's. Advice Author, first, made its own more restrictive rules. Second, the existence of monitoring the performance of law enforcement officers. Thirdly, the right to damages included in the judgment.Keywords: Application-Compensation-Defendant-Convict